A Review of the Tetrapod Track Record in China, with Special Reference to Type Ichnospecies： Implications for Ichnotaxonomy and Paleobiology - LOCKLEY, Martin G.; Jianjun, LI; Rihui, LI; MATSUKAWA, Masaki; HARRIS, Jerald D.; Lida, XING (Acta geologica Sinica (Beijing), 2013)
＂Splitting＂ and ＂lumping＂ are perpetual problems in vertebrate, especially dinosaur, ichnotaxonomy. Chinese dinosaur ichnotaxonomy, which began in 1940, provides a series of interesting case studies, highlighting the dual problems of historical and dubious ichnotaxonomy. Chinese Mesozoic tetrapod track types have been placed into 63 ichnospecies （one Triassic, 28 Jurassic, and 34 Cretaceous）, exclusive of other, non-type ichnospecies or ichnotaxa identified from China. Fifty-two （~83%） of these 63 tetrapod ichnospecies were placed in monospecific ichnogenera. At the ichnogenus level, we prune---either by recognizing nomina dubia or by synonymy--17 from the list of 53 dinosaurian ichnogenera （a 32% reduction）, leaving 36 ichnotaxa that we consider valid. Most of the cuts affect Jurassic theropod ichnotaxa, which are reduced from 23 to only nine because most ichnogenera are subjective junior synonyms of Grallator and Eubrontes. Fewer Chinese Cretaceous ichnotaxa （only six of 21 ichnogenera） are obvious nomina dubia or subjective synonyms, suggesting greater east Asian endemism during this time. Because ichnospecies differences are subtle, we provisionally retain ichnospecies as valid pending detailed comparative analyses of congeneric ichnospecies. This synthesis is long overdue and is necessary to address problems of historical and provincial ichnotaxonomy, which severely hamper comparisons of tetrapod ichnofaunas in space and time.